Group Exhibition-OPEN 2002, 5th International Exhibition of Sculptures and Installations, Lido, Venice, Italy - Antoniou, Klitsa (My University, 2026)
OPEN 2002, 5th International Exhibition of Sculptures and Installations, Lido, Venice, Italy, Curated by Pierre Restany